Miscellaneous Topics - Zaidi, Rehan (JavaScript Essentials for SAP ABAP Developers, 2017)
This chapter covers topics that are very useful but do not fit well in any of the earlier chapters. It starts with an overview of strict mode and how it affects the syntax check, as well as error handling in JavaScript. Next, you are provided tips related to code formatting and suggestions for using a naming convention for variables. A separate section explains debugging and troubleshooting JS programs. Last but not least, this chapter provides best practices for JS programming and offers some performance-improvement tips.